2015
DOI: 10.1016/j.jmaa.2015.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Networks for the weak topology of Banach and Fréchet spaces

Abstract: Please cite this article in press as: S. Gabriyelyan et al., Networks for the weak topology of Banach and Fréchet spaces, J. Math. Anal. Appl. (2015), http://dx.Abstract. We start the systematic study of Fréchet spaces which are ℵ-spaces in the weak topology. A topological space X is an ℵ 0 -space or an ℵ-space if X has a countable k-network or a σ-locally finite k-network, respectively. We are motivated by the following result of Corson (1966): If the space C c (X) of continuous realvalued functions on a Tych… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…Theorem 3.5 and Corollary 3.7 immediately imply the following result which might be also extracted from the proof of [31,Corollary 2.18] and is proved in [12].…”
Section: Nagata-smirnov Metrization Theorem Impliesmentioning
confidence: 55%
See 3 more Smart Citations
“…Theorem 3.5 and Corollary 3.7 immediately imply the following result which might be also extracted from the proof of [31,Corollary 2.18] and is proved in [12].…”
Section: Nagata-smirnov Metrization Theorem Impliesmentioning
confidence: 55%
“…Let us note that in the following theorem the implication (i) ⇔ (ii) generalizes [4, Theorem 1.9], the implication (i) ⇔ (iii) is proved in [12] and (i) ⇔ (v) follows from [24].…”
Section: Metrizability Conditions For Topological Spacesmentioning
confidence: 82%
See 2 more Smart Citations
“…In it is proved that if E is a Banach space whose strong dual is separable, then Ew is an ℵ 0 ‐space. In [, Corollary 5.6] it was shown that a Banach space which does not contain an isomorphic copy of ℓ 1 has separable dual if and only if Ew is an ℵ 0 ‐space. Next theorem extends this result to quasi‐(DF)‐spaces.…”
Section: Quasi‐(df)‐spacesmentioning
confidence: 99%